2021
DOI: 10.3390/app11114740
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Structural Optimization of Bearingless Permanent Magnet Slice Motor Based on Virtual Prototype in Ansoft Maxwell

Abstract: As a preliminary study for bearingless permanent magnet slice motor (BPMSM) development, an effective means for BPMSM mechanical structure optimization is proposed here by developing a virtual prototype based on Ansoft Maxwell to realize overall performance improvements. First, the sensitivity evaluation index of the candidate mechanical structural parameters for individual BPMSM performance is constructed for selection. Orthogonal tests are performed to determine the dominant mechanical structural parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The magnetic field finite element analysis of an obstacle blocking the permanent magnet structure was carried out using the Ansoft Maxwell module in the ANSYS software (Li et al, 2006; Shen et al, 2021), as shown in Figures 17–19.…”
Section: Simulation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic field finite element analysis of an obstacle blocking the permanent magnet structure was carried out using the Ansoft Maxwell module in the ANSYS software (Li et al, 2006; Shen et al, 2021), as shown in Figures 17–19.…”
Section: Simulation Analysismentioning
confidence: 99%
“…However, it also has slow crawling speed, large mass, is difficult to handle, and is inconvenient to steer. The leg-type wall-climbing robot proposed in Bian et al (2021) and Huo et al (2021) has a good obstaclesurmounting ability. However, its walking speed is slow, the control is relatively complex, and the efficiency is low.…”
mentioning
confidence: 99%
“…Taking the permanent magnet adsorption device on the driving wheel side as an example, two models were developed, as illustrated in Figure 11. The Ansoft Maxwell software (Li et al, 2006;Shen et al, 2021) was used to perform magnetic field finite element simulation analysis on the two adsorption models. The air solution domain was set to 15%.…”
Section: Comparative Analysis Of the Magnetic Circuit Designmentioning
confidence: 99%
“…The Ansoft Maxwell software (Li et al, 2006; Shen et al, 2021) was used to perform magnetic field finite element simulation analysis on the two adsorption models. The air solution domain was set to 15%.…”
Section: Parametric Simulation Analysis Of Permanent Magnet Adsorptio...mentioning
confidence: 99%
“…Wang et al proposed a multiobjective optimization method based on the genetic algorithm and magnetostatic FEA 2D model to optimize the shape design parameters of linear proportional solenoids [40]. Shen et al proposed an effective optimization method for mechanical structure of a bearing less permanent magnet slice motor (BPMSM), which uses the gradient descent method to obtain a linear regression model, and the genetic algorithm was used to solve it [41]. For the research of TMAAG in this paper, the method where a regression model is obtained through neural network and then solved by genetic algorithm is selected, which considers both simplicity and accuracy simultaneously.…”
Section: Introductionmentioning
confidence: 99%